Non-volant mammals from the protected areas associated to hydroelectric projects on the eastern slope of the northern Cordillera Central, Colombia (2017)
ABSTRACT: The northern part of the Cordillera Central in Colombia has been recognized as a region of particular relevancy in vertebrates biodiversity. We provide a list of non-volant mammal species in Jaguas and San Carlos, two protected areas around hydroelectric projects on the eastern slope of the Cordillera Central in Antioquia. As part of an ongoing monitoring project, we obtained records from a standardized survey in 2011 and sporadic surveys in 2014–2015 (capture and non-invasive methods), and from the revision of voucher specimens. From 132 records we generated a list of 34 species, 22 species in Jaguas and 27 in San Carlos, belonging to 20 families and seven orders. We record the occurrence of four endemic and four threatened species, including the endemic and Endangered Tamarin, Saguinus leucopus, highlighting the importance of these protected areas for mammal conservation in this highly diverse region.